2021
DOI: 10.1039/d1ta02814f
|View full text |Cite
|
Sign up to set email alerts
|

Pre-programed hydroxy double salt templates for room-temperature controlled synthesis of mixed-metal zeolitic imidazolate frameworks

Abstract: Mixed-metal metal-organic frameworks (mmMOFs) are promising for many envisioned applications such as gas adsorption, separations, catalysis and electrochemical energy storage. However, it is still very challenging to achieve controlled stoichiometric...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 56 publications
3
12
0
Order By: Relevance
“…[121] In Zhao et al's work the MMMs of Pebax-2533 containing the ZIF fillers with varying metal ratio was spun coated on alumina substrate with a thickness less than 3 μm. [45] The MMMs containing ZIF-7 with Co : Zn ratio of 3 : 1 exhibited CO 2 permeance up to 115.6 GPU (346.8 Barrer) much higher than the pure Pebax-2533 and a high CO 2 /N 2 selectively of 36.5. The reduced thickness of membrane and increased selectivity of CO 2 due to its interaction with ZIF filler are explained to be the reason behind improved performance.…”
Section: Gas Separationmentioning
confidence: 94%
See 4 more Smart Citations
“…[121] In Zhao et al's work the MMMs of Pebax-2533 containing the ZIF fillers with varying metal ratio was spun coated on alumina substrate with a thickness less than 3 μm. [45] The MMMs containing ZIF-7 with Co : Zn ratio of 3 : 1 exhibited CO 2 permeance up to 115.6 GPU (346.8 Barrer) much higher than the pure Pebax-2533 and a high CO 2 /N 2 selectively of 36.5. The reduced thickness of membrane and increased selectivity of CO 2 due to its interaction with ZIF filler are explained to be the reason behind improved performance.…”
Section: Gas Separationmentioning
confidence: 94%
“…Zhao et al. found that Co : Zn ratio of resulting BMOF could be controlled more efficiently by HDS conversion strategy in comparison to one pot synthesis [45] . Similarly Dong et al reported that the composition of BMOF was determined by the composition of layered double hydroxide (LDH) [46] …”
Section: Synthesis Of Bmofmentioning
confidence: 99%
See 3 more Smart Citations